Penerapan Teori Kebutuhan Hubungan Melalui Media Sosial Pada Siswa SMK Swasta Kesehatan Ganda Husada Tebing Tinggi - Mutmainnah, Fazri (Universitas Muhammadiyah Sumatera Utara, 2025)
This study discusses the role of social media in meeting the social relationship needs of students at SMK Swasta Kesehatan Ganda Husada Tebing Tinggi. Social media is used as a means of communication, social interaction, and self-development, but it can also have negative impacts if not used wisely. This study uses a qualitative method with a descriptive approach. Data were collected through interviews with four grade XI nursing students selected based on the intensity of their social media use. The results showed that social media helps students maintain communication with friends and family, increases self-confidence through social validation, and provides access to educational content that supports self-development. However, excessive use has an impact on disrupted sleep patterns, reduced physical activity, and increases the risk of fraud and account misuse. In addition, interactions on social media can also affect students' psychological conditions, both positively and negatively